THE EFFECT OF USING GRAPHIC ORGANIZER ON THE EIGHTH GRADE STUDENTS’ READING COMPREHENSION ACHIEVEMENT: A EXPERIMENTAL STUDY - Dian fitrianingsih (Graduate Program, University of Islam Malang, 2020)
Abstract Reading as one of language skills, is very important. By reading ability the students will be able to understand and transfer the contents of reading passage. Here, this study is employed quasi experimental research. It uses posttest design only. To accessible population of this study was eighth grade student of MTs Negeri 10 Banyuwangi. The researcher conducted this study on the even of semester of 2018/ 2019 academic year. The two of eight classes, were taken to be sample of study. It was VIII D which consists of 32 students as experimental group. Then, the control group was VIII C, it consists of 32 students. The experimental group taught by using Graphic Organizer. Meanwhile, the control group was taught by conventional teaching strategy. The researcher prepared a set of reading text in the form of multiple choices as the instrument. To analyze the data, independent T- test was used to know the difference of the learning achievement of two groups. By employing the independent T-test analysis in SPSS 20, the result of computations shows that the score of t was 0.039 that was lower than significant level 5 % (0.05). Based on these T values can be concluded that there is significant difference of using Graphic Organizer on the students’ reading comprehension achievement. In other words, the students who taught by using graphic organizers achieved reading comprehension better than those who were taught conventional teaching strategy. Some recommendations that were given to the teachers and school are that the teaching of reading skill, implement graphic organizer as the alternative strategy, and give more emphasis on the reading technique of making inference of the reading content. Keywords: the effectiveness, graphic organizer strategy, reading comprehension